2020
DOI: 10.1590/0034-7167-2019-0823
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and perinatal depressive symptoms: an integrative review

Abstract: Objective: to investigate occurrence and risk factors for common mental disorders and perinatal depressive symptoms. Methods: an integrative literature review using CINAHL, Embase, PubMed, PsycINFO, and LILACS, looking for studies conducted between 2014 and 2019. Data collection took place between June and July 2019. Health Sciences Descriptors (DeCS) and Medical Subject Heading (MeSH) were used in the search strategies employed in each database. Results: thirteen articles were included. Most studies were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
3
0
4
Order By: Relevance
“…However, the criteria adopted to define a case of mental disorder are among those with the biggest influence on the discrepancies found. Although the most widely used instruments for screening these problems in Brazil, and in the international literature, are the SRQ-20 and the EPDS, the cutoff points adopted diverged significantly between the studies, which explains the variability between our results and the literature on the subject 5 . In addition, some studies adopt concepts of CMD that diverge from those established by WHO 2 , 5 .…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, the criteria adopted to define a case of mental disorder are among those with the biggest influence on the discrepancies found. Although the most widely used instruments for screening these problems in Brazil, and in the international literature, are the SRQ-20 and the EPDS, the cutoff points adopted diverged significantly between the studies, which explains the variability between our results and the literature on the subject 5 . In addition, some studies adopt concepts of CMD that diverge from those established by WHO 2 , 5 .…”
Section: Discussionmentioning
confidence: 61%
“…No entanto, os critérios adotados para definir um caso do problema estão entre os que mais influenciam nas discrepâncias encontradas. Apesar de os instrumentos mais utilizados para rastreamento desses problemas no Brasil e na literatura internacional serem o SRQ-20 e o EPDS, os pontos de corte adotados divergiram significativamente entre os estudos, o que explica a variabilidade entre nossos resultados e a literatura sobre o tema 5 . Ademais, é possível verificar a adoção de diferentes conceitos de TMC em alguns estudos, diferentes daqueles estabelecidos pela OMS 2 , 5 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The prevalence of depression and anxiety in women is 1.5–2.5 times higher than that in men ( 8 ). Additionally, gender-specific disorders are more significant in women, such as perinatal MD ( 9 ). It is reported that the disease mechanism of inflammatory dysregulation may lead to MD ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%